Penguatan Literasi Keagamaan Anak Melalui Bimbingan Iqro' dan Bahasa Arab di Desa Marindal II Patumbak - Fadilla, Mutia; Naimi, Nadlrah (Journal of Community Sustainability, 2025)
The Community Service Program (KKN) conducted in Marindal II Village, Patumbak, aimed to strengthen children's religious literacy through Iqro' and Arabic language guidance. This village holds great potential for enhancing children's understanding of religious teachings, yet still faces challenges in delivering effective and engaging methods for teaching Qur'anic reading and Arabic. This study employed a qualitative approach using participatory observation and in-depth interviews with students and local community members. The learning process applied interactive methods that combined educational games and contextual approaches to create a fun and accessible learning environment. The results showed a significant improvement in the children’s ability to read Iqro' and recognize basic Arabic vocabulary. The children demonstrated high learning motivation, and the community responded positively to the program as a valuable effort in nurturing the religious character of the younger generation. This program is expected to serve as a model for developing creative and sustainable religious literacy initiatives in other rural areas, adapted to local needs and contexts.